Pengaruh Motivasi Belajar Terhadap Minat Belajar Siswa Akuntansi Dan Keuangan Lembaga Kelas X SMK Negeri 1 Banjarmasin - Husaini, Fahry; Hasanah, Mahmudah; Rizky, H. Maulana; Ratumbuysang, Monry Fraick Nicky Gillian (Universitas Negeri Surabaya, 2024)
Delays in submitting individual assignments often occur due to a lack of learning initiative. Learning motivation can foster enthusiasm for learning so that students are encouraged to carry out learning activities and provide passion or enthusiasm for learning. Interest is an initial movement so that students have an interest in the material being taught which can be used to achieve the desired learning goals. The aims of this research are: (1) to determine students' learning motivation, (2) to determine students' interest in learning, and (3) to determine the influence of learning motivation on students' interest in learning. The method used is causal associative with a quantitative approach. The population of this study was 141 students of class x accounting and finance at SMK Negeri 1 Banjarmasin. The analysis used is simple linear regression. Based on the results of the regression test, it can be shown with a level of significance or probability that there is a significant influence between the variable learning motivation on interest in learning.